INVENTARISASI JENIS JENIS BELALANG (Ordo Orthoptera) DI DUSUN TIBANG DESA HITU MESSING KABUPATEN MALUKU TENGAH - Lapu, Petrus; Mainassy, Meillisa; Pelu, Evy (BIOMA : JURNAL BIOLOGI MAKASSAR, 2025)
Abstract Locusts that can be found in Indonesia include Belalang Kumbara (Locusta migratoria), Belalang Daun (Phyllium fulchrifolium), Belalang Kayu (Valanga nigricornis), Belalang Sembah (Hierodula vitrea), Belalang Hijau (Oxya serville) and Belalang Ranting (Phobaeticus chani). Tibang Hamlet is located in Hitu Village, Central Maluku Regency. This hamlet has a natural forest which is the habitat of several types of locusts to find food and survive. The purpose of this study was to determine the types of locusts and also forest vegetation that is the habitat of locusts (Order Orhtoptera) in Tibang Hamlet. The method used is descriptive qualitative and field observations that can describe the description of grasshopper species and vegetation. The results of the study found 3 types of grasshoppers and 6 types of vegetation as follows grasshoppers are Wood Grasshopper (Valanga nigrocornis) Kumbara Grasshopper (Locusta migratoria) Green Grasshopper (Oxya serville) while 6 types of vegetation are Awar-awar (Ficus septica), Kirinyuh plant (Chromolaena odorata), Mengkirai plant (Trema orientalis), Wedelia plant (Wedelia sp), Pecut kuda plant (Stachytarpheta jamaicensis), and Bandotan plant (Ageratum conyzoides).